The Effect of A Clinical Practice Guideline on Abdominal Pain Triage in An Outpatient - พิมพ์สังข์, สุธาสินี; กรรมบุตร, จีราภรณ์; นิรัตธราดร, มยุรี (Journal of The Royal Thai Army Nurses, 2019)
Abdominal pain is a common symptom in outpatients that involve in many organs and is caused by several factors. The most inaccuracy in abdominal pain triage were reported in the Thammasat University Hospital database. This preliminary study was a quasi-experimental research which had the purpose to examine the effects of a clinical practice guideline on abdominal pain triage in outpatients. The purposive samples were 6 triage nurses. The research instruments used in this study consisted of the clinical practice guideline and an instruction manual for abdominal pain triage in outpatients, which were developed by using the IOWA model and examined by 3 experts and a satisfaction questionnaire. The reliability of the guideline was confirmed with an inter-rater reliability coefficient of 1. The preliminary data were analyzed using descriptive statistics, chi-squared, and Fisher’s exact test. The result revealed that triage nurses had high satisfaction in overall of using such guideline. The guideline consist of clear steps of triage is helpful, convenience and improve the nurse confidence in triage accuracy. Anyway, this study show no significant difference in statistic (X2 = .608, p = .944). comparing before and after using the guideline. Recommendation; Triage nurse may use clinical guideline in abdominal pain triage for outpatient as result of this evidence base to improve their nursing care provision. The use of this guideline shall be continued further study and development.